Characteristic and Physical Stability of Anti-Aging Green Tea Extract (GTE) on NLC with Argan Oil as Liquid Lipid - Anita Natalia Suryawijaya; Tutiek Purwanti; Djoko Agus Purwanto; Widji Soeratri (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Green tea extract is a hydrophilic antioxidant that is difficult to penetrate. A nanostructured lipid carrier (NLC) delivers a system consisting of solid-liquid lipids that can improve penetration. Argan oil is a vegetable oil that can be used as a liquid lipid in NLC, reducing particle size and increasing penetration by hydrating the skin. Objective: To determine the formula of NLC green tea extract (NLC-GTE) with liquid lipid argan oil, which has good characteristics and is stable. Methods: Preparation of NLC-GTE used the High Shear Homogenization with solid lipids (cetyl palmitate-glyceryl stearate) - liquid lipids (argan oil) NLC-GTE1 (50:50), NLC-GTE2 (70:30), and NLC-GTE3 (90:10). Characteristic tests included organoleptic, pH, particle size (PS), and polydispersity index (PI). The physical stability test (organoleptic, pH, PS, and PI) used the thermal cycling method (3 cycles six days). Result: NLC-GTE1 – NLC-GTE2 has an odor of argan oil. NLC-GTE3 has odorless. NLC-GTE1 – NLC-GTE3 has a pH scale from 5.782-5.784; PS ranges from 359.73–432.56 nm; PI ranges from 0.175-0.257. The statistical analysis results showed no significant difference between NLC-GTE1 – NLC-GTE3 in pH and PI, there was a significant difference in PS NLC-GTE1; NLC-GTE2 against NLC-GTE3. Physical stability test NLC-GTE2 – NLC-GTE3 phase separation occurs. The statistical analysis results showed no significant difference in pH values NLC-GTE1 – NLC-GTE3 "‹"‹before and after storage; there was a significant difference in NLC-GTE3 before and after storage. Conclusion: NLC-GTE1 was a formula with good characteristics and stability.